Development and validation of a new spectrophotometric method for the determination of acyclovir (2012)
A new spectrophotometric method has been developed for the analysis of acyclovir in bulk and dosage forms. The method is based on the diazo coupling reaction between diazotized acyclovir and p-dimethylaminobenzaldehyde (DMAB). Spot tests and thin layer chromatographic analysis confirmed the formation of a greenish-yellow adduct which was stable in the laboratory environment for more than three hours. Critical factors affecting optimal detector response were identified and optimized. The optimal temperature and coupling reaction time were established at 50oC and 10 min. The azo adduct was determined at 404 nm where neither diazotized acyclovir nor DMAB has any significant absorptivity. Methanol was found as the best diluting solvent after coupling. The assays of acyclovir were linear over the range 1.81-9.06 μg/mL with a correlation coefficient of 0.9998 and limit of detection of 0.024 μg/mL. The method was accurate (error < 3 %) and precise (RSD < 2.7 %) over three days assessment. There was no interference from commonly used excipients. The method was successfully applied to the determination of acyclovir in tablets and creams with similar accuracy to the official USP spectrophotometric method. The method is rapid, simple and cost-effective and could find application in the in-process quality control of acyclovir.